Relationship between Psychological Factors with Cooperation and Satisfaction in Fixed Orthodontic Patient - Tahere Ahmadpour; Nasim Esnaashar; Hadi Farhadi; Nafiseh Shirani (مجله دانشکده دندانپزشکی اصفهان, 2022)
Cooperation in orthodontics is one of the most important predictors of treatment outcome. Evaluation of patient satisfaction is a suitable criterion for the evaluation of treatment quality of the patients and the relationship between physician and patient. In this study, the link between some personality traits of patients and their cooperation in orthodontic treatment is assessed.Materials & Methods:In this descriptive study, 135 patients who were referred to the orthodontic department at the School of Dentistry of Isfahan Azad University for fixed orthodontic treatment were selected. The correlation between 5 psychological factors of Costa and McCrae personality theory with the level of cooperation and satisfaction of patients during orthodontic treatment was assessed by NEO-FFI questionnaire, and OPCS questionnaire to measure patient cooperation 2 months and 6 months after treatment and satisfaction questionnaire. Data were analyzed using Pearson, Spearman and Regression correlation coefficients.Results:The mean cooperation score was not significantly different between 2 months and 6 months after starting treatment (p value = 0.66). The satisfaction score of treatment was directly related to the score of the responsible factor of responsibility (p value< 0.01) but was not significantly related to the scores of other personality traits factor (p value > 0.05).Cooperation score 2 months and 6 months after starting treatment was not significantly related to personality trait factor scores (p value > 0.05).There was no significant relationship between cooperation score 2 months (p value = 0.57) and 6 months after starting treatment (p value = 0.99) with treatment satisfaction score.Conclusion:There is no relationship between orthodontic patients' cooperation and their personality type. A direct relationship between orthodontic patients' satisfaction and the score of the personality factor of responsibility was seen